2007
DOI: 10.2332/allergolint.c-06-51
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Ortho-phthalaldehyde-induced Anaphylaxis after Laryngoscopy: Detection of Specific IgE in Serum

Abstract: Physicians and co-medical workers need to be aware of potential allergens to which patients may be exposed during routine medical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 9 publications
2
28
0
1
Order By: Relevance
“…This sample was analyzed for OPA-specific immunoglobulin E (IgE) and immunoglobulin G (IgG) antibodies [Suzukawa et al 2007] to assess past exposures to OPA. Details of the antibody analyses are included in Appendix C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This sample was analyzed for OPA-specific immunoglobulin E (IgE) and immunoglobulin G (IgG) antibodies [Suzukawa et al 2007] to assess past exposures to OPA. Details of the antibody analyses are included in Appendix C.…”
Section: Methodsmentioning
confidence: 99%
“…Anaphylaxis (a rapidly progressing, potentially life-threatening allergic reaction) was seen in patients who had medical procedures with endoscopes disinfected with OPA. Subsequent immunological testing indicated that OPA was the inciting agent [Suzukawa et al 2007;Cooper et al 2008;Pala and Moscato 2013]. Following reports of patient sensitization, reports of adverse occupationally related health effects surfaced.…”
Section: Ortho-phthalaldehyde and High Level Disinfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVC, polyurethane and siicone that tend to absorb disinfectants. While reports on the adverse effects of residual disinfectants were thought to be due to poor rinsing, the absorption by materials and toxicity related to the later release of disinfectants should not be ignored, as anaphylaxis and other sorts of allergic reactions have been reported to be due to this phenomenon Suzukawa et al, 2006;Suzukawa et al 2007;Soko, 2004;Zeiger et al, 2005 .…”
Section: Figmentioning
confidence: 99%
“…As these disinfectants are frequently used during endoscopic procedures, there have been reports on the adverse effects of their residues, especially with OPA, since it causes discoloration of the skin and mucous membranes, irritation, anaphylaxis and other allergic reactions Abdulla and Adams, 2007;Arrandale et al, 2012;Cooper et al, 2008;Miyajima et al, 2010;Suzukawa et al, 2007;Venticinque et al, 2003 . These …”
mentioning
confidence: 99%